High G2 and S‐phase expressed 1 expression promotes acral melanoma progression and correlates with poor clinical prognosis. Issue 6 (11th May 2018) - Xu, Tianxiao; Ma, Meng; Chi, Zhihong; Si, Lu; Sheng, Xinan; Cui, Chuanliang; Dai, Jie; Yu, Sifan; Yan, Junya; Yu, Huan; Wu, Xiaowen; Tang, Huan; et al.
Abstract : G2 and S‐phase expressed 1 (GTSE1) regulates cell cycle progression in human cancers. However, its significance and mechanism of action in acral melanoma (AM) remain unknown. In the present study, we found that GTSE1 expression was upregulated in advanced stage/metastatic AM tissues and metastatic cell lines, and correlated with higher stage ( P  = .028) and poor disease‐free survival (DFS) in patients with AM ( P  = .003). Cox regression assays validated GTSE1 expression to be an independent prognostic factor of DFS for patients with AM ( P  = .004). Ectopic expression of GTSE1 enhanced primary AM cell proliferation, invasion, and migration. Loss‐of‐function in GTSE1 attenuated metastatic AM cell proliferation and metastatic ability in vitro and in vivo. We additionally observed that inhibition of migration and invasion occurred concomitantly with a GTSE1 knockdown‐mediated increase in E‐cadherin and decreases in N‐cadherin and Slug. We further showed that integrin subunit alpha 2 (ITGA2) interacts with GTSE1 and is a downstream effector of GTSE1. Further, ITGA2 levels were positively correlated with GTSE1 expression in human AM tissues. Ectopic ITGA2 expression rescued siGTSE1‐mediated inhibition of migration and invasion, thereby restoring epithelial‐to‐mesenchymal transition (EMT). In conclusion, GTSE1 expression promotes AM progression and correlates with clinical outcomes of patients with AM, and may represent a promising therapeutic target to suppress AM progression. Abstract : In this study, we show that the cell cycle regulator G2 and S‐phase expressed 1 (GTSE1) is overexpressed in AM, causes increased proliferation, migration, invasion, and metastasis, and is strongly correlated with poor prognosis. We believe that our study makes a significant contribution to the literature because it provides in vitro, in vivo, and clinical evidence for a novel target in the treatment of AM.